MWA Observations of the EOR1 Field. Issue Volume 12:Issue S333(2017) (8th May 2018) - Pindor, Bart
Abstract: The EOR1 field at (RA, DEC)=(4hrs, −30.0°) is one of the main targets of the MWA EOR experiment. It is notable for being in one of the coldest regions of the southern radio sky, as well as for containing the bright radio galaxy Fornax A. We report an early demonstration that the distance of this field from the Galactic Centre may make it a prime field for EOR observations.